Mammalian diseases of phosphatidylinositol transfer proteins and their homologs - Nile, Aaron H; Bankaitis, Vytas A; Grabon, Aby (Clinical lipidology, 2010)
Inositol and phosphoinositide signaling pathways represent major regulatory systems in eukaryotes. The physiological importance of these pathways is amply demonstrated by the variety of diseases that involve derangements in individual steps in inositide and phosphoinositide production and degradation. These diseases include numerous cancers, lipodystrophies and neurological syndromes. Phosphatidylinositol transfer proteins (PITPs) are emerging as fascinating regulators of phosphoinositide metabolism. Recent advances identify PITPs (and PITP-like proteins) to be coincidence detectors, which spatially and temporally coordinate the activities of diverse aspects of the cellular lipid metabolome with phosphoinositide signaling. These insights are providing new ideas regarding mechanisms of inherited mammalian diseases associated with derangements in the activities of PITPs and PITP-like proteins.